A new indicator for assessing fishing ecological pressure using multi-source data: A case study of the South China Sea - Yanan Guan; Xi Zhang; Gui Gao; Chenghui Cao; Zhongwei Li; Shihao Fu; Genwang Liu (Ecological Indicators)
The assessment of fisheries resources development is an important basis for formulating marine fisheries management regulations and arranging fisheries production activities reasonably, which is of great significance for improving the economic benefits of the ocean. However, due to limitations in available data and assessment techniques, current assessments often face issues such as poor timeliness, low spatiotemporal resolution, and limited evaluation indicators. This study unveils a groundbreaking indicator, termed Fishery Ecological Pressure (FEP), which transcends existing frameworks by holistically integrating diverse factors, encompassing variations in fishing activities and the inherent carrying capacity of the marine environment. FEP harnesses multi-source marine remote sensing data to rapidly quantify the spatiotemporal impacts of fishing activities on the marine ecosystem, thereby effectively addressing the limitations of current assessments. Using this indicator, we conducted detailed assessments of the fishery ecological pressure in the South China Sea (SCS), along with a thorough analysis of its spatiotemporal characteristics and variations. The results show that in September, the fishery resources in most areas of the SCS were in a state of sustainable development. However, certain areas in the northern Nansha fishing ground faced significant pressures on fisheries resource exploitation, requiring immediate actions to ensure sustainable development of fisheries resources in this area. This research offered a more precise perspective on fisheries resource development, thereby providing decision-making support for marine ecological protection.